Growth-regulating factor 15-mediated vascular cambium differentiation positively regulates wood formation in hybrid poplar (Populus alba × P. glandulosa) - Zhou, Houjun; Song, Xueqin; Lu, Meng-Zhu (Frontiers in Plant Science, 2024)
Hybrid poplars are industrial trees in China. An understanding of the molecular mechanism underlying wood formation in hybrid poplars is necessary for molecular breeding. Although the division and differentiation of vascular cambial cells is important for secondary growth and wood formation, the regulation of this process is largely unclear. Here, we report that PagGRF15 from hybrid poplar (Populus alba × P. glandulosa), a growth-regulating factor, plays a critical role in the regulation of vascular cambium activity. PagGRF15 was expressed predominantly in the cambial zone of vascular tissue. Overexpression of mPagGRF15 (the mutated version of GRF15 in the miR396 target sequence) in Populus led to decreased plant height and internode number. Further stem cross sections showed that the mPagGRF15 OE plants exhibited significant changes in vascular pattern with an increase in xylem and a reduction in phloem. In addition, cambium cell files were decreased in the mPagGRF15 OE plants. However, dominant suppression of the downstream genes of PagGRF15 using PagGRF15-SRDX showed an opposite phenotype. Based on the RNA-seq and ChIP-seq results, combining qRT-PCR and ChIP-PCR analysis, candidate genes, such as WOX4b, PXY and GID1.3, were obtained and found to be mainly involved in cambial activity and xylem differentiation. Accordingly, we speculated that PagGRF15 functions as a positive regulator mediating xylem differentiation by repressing the expression of the WOX4a and PXY genes to set the pace of cambial activity. In contrast, PagGRF15 mediated the GA signaling pathway by upregulating GID1.3 expression to stimulate xylem differentiation. This study provides valuable information for further studies on vascular cambium differentiation mechanisms and genetic improvement of the specific gravity of wood in hybrid poplars.